2017
DOI: 10.1039/c7tc04151a
|View full text |Cite
|
Sign up to set email alerts
|

Stable monolayer α-phase of CdTe: strain-dependent properties

Abstract: CdTe is a well known and widely used binary compound for optoelectronic applications. In this study, we propose the thinnest, free standing monolayer of CdTe which holds the tetragonalPbO (α-PbO) symmetry. The structural, electronic, vibrational and strain dependent properties are investigated by means of first principles calculations based on density functional theory. Our results demonstrate that the monolayer α-CdTe is a dynamically stable and mechanically flexible material. It is found that the thinnest mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…In the latter case, the unstable bulk (wurtzite) phase possessed strong imaginary modes. [7] After submission of this work, our attention was brought to work by Unsal et al, [23] where a stable α-phase of CdTe was reported (Figure 6). It is interesting to note an important similarity between them, namely, the Cd atomic planes are sandwiched between Te atomic planes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, the unstable bulk (wurtzite) phase possessed strong imaginary modes. [7] After submission of this work, our attention was brought to work by Unsal et al, [23] where a stable α-phase of CdTe was reported (Figure 6). It is interesting to note an important similarity between them, namely, the Cd atomic planes are sandwiched between Te atomic planes.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6. The fully relaxed structure of monolayer α-CdTe [23] shown in different projections. The lower-right panel shown an axonometric image of the structure.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In 2017, researchers predicted a α-CdTe (tetragonal-PbO structure) monolayer with low formation enthalpy and excellent dynamic stability. The novel electronic structure endows 2D α-CdTe with a promising application potential in optoelectronic devices . In 2020, Naseri et al built a planar 2D CdTe, with the use of the predicted CdS honeycomb structure .…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, strain modulation and element doping in the 2D ZnS have also been carried out. 15,19,20 Recently, a tetragonal phase has been reported in monolayer CdTe, 21 CdSe, 22 CdS 22 and ZnSe; 23 as one of these II–VI compounds, monolayer ZnS also possesses a similar structure. 24 However, the knowledge of monolayer tetragonal ZnS remains very limited, 25 which severely impedes its practical application.…”
Section: Introductionmentioning
confidence: 99%